Boundary Breaking: An Emergent Model for Leadership Development - Webber, Charles; Robertson, Jan (Education Policy Analysis Archives, 1998)
We summarize the results of a cross-cultural on-line project for graduate students in educational leadership at the University of Calgary in Canada and the University of Waikato in New Zealand. A conceptual framework for the collaborative Internet project is presented in conjunction with a summary of relevant literature and participant views of the project. Finally, the authors propose a model for on-line graduate learning in educational leadership with the following components: construction of meaning, provision of a forum for discussion, validation of personal knowledge, generative learning, formal and informal leadership, sense of community, and international perspectives.